"Rapprocher les lieux du pouvoir": The Québec Labour Movement and Québec Sovereigntism, 1960-2000 - Güntzel, Ralph (Labour/Le Travailleur, 2000)
Abstract The article examines the evolution of the positions Quebec's three major trade union centrals — the Fédération des travailleurs et travilleuses du Québec (FTQ), the Centrale des syndicats nationaux (CSN), and the Centrale des syndicats du Québec (CSQ) — have taken on the question of Québec sovereignty since 1960. In the course of the four decades since the emergence of the modern sovereigntist movement, the three centrals adopted increasingly sympathetic attitudes toward sovereigntism and eventually became stalwarts of the sovereigntist coalition. In the process Québec labour activists shed their fears about the economic repercussions of sovereignty and espoused the notion of a sovereign Québec nation-state mainly because they came to perceive it as a tool to improve conditions for implementing social-democratic and labour-oriented policies.